Diseño e implementación de un entorno virtual de aprendizaje utilizando kompozer para la enseñanza de los estudiantes del segundo año de bachillerato técnico polivalente en informática, en la asignatura de elaboración y administración de sitios web del colegio de bachillerato "Dr. Camilo Gallegos Domínguez" de la ciudad de Arenillas provincia del Oro año lectivo 2015 –2016 - Cun Rueda, Maricela de Jesús (2016)
In this thesis entitled Diseño e Implementación de un Entorno Virtual de aprendizaje utilizando Kompozer para la enseñanza de los estudiantes del segundo año de Bachillerato Técnico Polivalente en Informática, en la asignatura de Elaboración y Administración de sitios web del Colegio de Bachillerato "Dr. Camilo Gallegos Domínguez" de la ciudad de Arenillas provincia de El Oro Año Lectivo 2015 – 2016 In the educational field where this research was conducted was evident lack of knowledge about the benefits we provide virtual classrooms in the educational field by the teachers, and non-use of free software as an alternative to the teaching process - learning, an advantage of the virtual classroom is to complement the class should be given space for the student to cope and be generating ideas, was carried out with the general aim Discover the advantages of using a Virtual learning Environment in the field education, with Kompozer tool for sophomores Technical College High School School "Dr. Camilo Gallegos Dominguez " The study population was students, teachers Polivalente Second Year Bachelor in Computer and Technical Teachers' Service Area, the following methodology was used by applying the deductive, inductive, analytical, synthetic Scientific methods. The results of the survey of students about whether they know about EVA 33% said yes, while 67% are unaware of the issue, to ask them if they have used a virtual learning environment in their teaching 27% answered no and 3% said yes, it was evident that the classes are very traditional, to conduct the survey on teachers if they know a virtual learning environment 50% said no and 50% said yes. In conducting the interviews the Teachers' Service area whether they have ever used a platform of virtual learning environment in the process of teaching - learning, they stated that not 100%, due to lack of technological equipment in the institution you can not implement Tic´s. This project focuses on collecting, compiling the most relevant information of Virtual Learning Environments and design a basic platform with Kompozer tool is a free software, so that it is an important contribution in the field of education, to reinforce knowledge acquired in the physical classroom and encourage students to do research and thoughtful, generating their own ideas and contributing their opinion to the issue presented.